Analisis Kebijakan Kompensasi dan Benefit Terhadap Kepuasaan Pegawai di PT Pegadaian Persero Cabang Sape - Indri Rahayu; Rahmatia Rahmatia; Mawar Hidayanti (Indo Publishing, 2026)
This study aims to analyze the effect of compensation policy and benefits on employee job satisfaction at PT Pegadaian (Persero) Sape Branch. The background of this study is based on differences in employees' perceptions of the compensation and benefits system implemented by the company, particularly between permanent employees and outsourced (forting) employees, which may affect their level of job satisfaction. This research employed a quantitative approach with an associative research design. The population consisted of 40 employees, all of whom were selected as the research sample using the saturated sampling technique. Data were collected through a questionnaire using a Likert scale. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), as well as correlation and coefficient of determination analyses with the assistance of SPSS version 26. The results indicate that the compensation policy has a positive and significant effect on employee job satisfaction, with a t-value of 2.418 and a significance value of 0.004 (<0.05). Benefits also have a positive and significant effect on employee job satisfaction, with a t-value of 3.423 and a significance value of 0.002 (<0.05). Simultaneously, compensation policy and benefits have a significant effect on employee job satisfaction, as indicated by an F-value of 24.295 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) is 0.668, indicating that 66.8% of the variation in employee job satisfaction can be explained by compensation policy and benefits, while the remaining 33.2% is influenced by other factors not examined in this study. In conclusion, the better the company's compensation policy and benefits, the higher the level of employee job satisfaction. Therefore, PT Pegadaian (Persero) Sape Branch is recommended to continuously improve its compensation policy and benefits in a fair, transparent, and employee-oriented manner to enhance job satisfaction and support the achievement of organizational goals.